กฎหมายและการปฏิบัติเกี่ยวกับการคุ้มครองสิทธิและสวัสดิการของผู้สูงอายุไทย - บุญโสภาคย์ ประสาน; นธกิจไพศาล ณปภัช; ธรรมนิจกุล ณัฐนันท์; สุวรรณลพ สิทธิชัย (KASEM BUNDIT JOURNAL, 2021)
PURPOSES: To review laws on and implementation of the elderly’s rights and welfare in some foreign countries and to analyse laws on and implementation of Thai elderly’s rights and welfare. METHODS: Documentary research and critical analysis. RESULTS: The study has revealed that the Act on the Elderly B.E. 2546 and the National Plan for Older Persons of Thailand provide measures to certify and protect rights and welfare of the elderly in various aspects. At present, however, the implementation concerning the protection of Thai elderly’s rights and welfare is not effective as it should be, and most of Thai local governments do not pay sufficient attention on elderly’s welfare. CONCLUSIONS: Measures of Thai elderly’s welfare and quality of life arrangement should be reformed basing on the following three principles: The authority and duty on Thai elderly’s welfare and quality of life arrangement should be decentralized from the central government and state agencies to local government organizations. Law on Long-term Care Insurance should be enacted. The elderly care tasks should be assigned as the community - based services.